التحليل عن طريقة العرض (سوروجان) في القدرة على قراءة كتاب فتح القريب لطلاب الصف الحادي عشر بمعهد سلالم الفضلاء سيمالونجون - Nisa, Khoirun; Lubis, Zulfahmi (Jurusan Pendidikan Bahasa Arab, 2024)
The problem experienced by class 11 students at the Salalimul Fudhola Islamic Boarding School is that they still have difficulty placing nahwu and shorof when reading books. This research focuses on the Sorogan method used in the Islamic boarding school to overcome the students’ difficulties, especially in reading the book Fathul Qarib. The aim of this research is to determine the application of the Sorogan method, supporting and inhibiting factors, and its impact on the ability to read the book Fathul Qarib of grade 11 students. This research uses a qualitative approach with descriptive methods, and data is collected through observation, interviews and documentation. Data analysis techniques refer to Miles & Huberman, including data reduction, data presentation, and drawing conclusions. The research results showed that the Sorogan method was applied with students taking turns facing the teacher, reading, translating and explaining the contents of the book Fathul Qarib. One of the supporting factors is the teacher’s strong desire to preserve the study of the yellow book, while the inhibiting factor is that some students do not study before sorogan. The Sorogan method has proven to be effective in improving students’ ability to read the book Fathul Qarib. It can be concluded that the Sorogan method plays an important role in the success of improving the ability to read books among students.